The myth of pulmonary Raynaud's phenomenon: the contribution of pulmonary arterial vasospasm in patients with systemic sclerosis related pulmonary arterial hypertension. Issue 12 (16th November 2004) - Mukerjee, D; Yap, L B; Ong, V; Denton, C P; Howells, K; Black, C M; Coghlan, J G
Abstract : Objective: To investigate the contribution of cold induced pulmonary vasospasm by peripheral and central cold stimulus in exacerbating pulmonary arterial hypertension (PAH) in patients with systemic sclerosis undergoing cardiac catheterisation. Methods: In a prospective pilot study, 21 patients with systemic sclerosis and catheter proven PAH had mean pulmonary artery pressure (mPAP), pulmonary vascular resistance (PVR), and cardiac output (CO) measured before and after peripheral (hand immersion into cold water at 10–15°C for two minutes if tolerated) and central (direct cold water at 4°C injected into the right atrium) cold pressor challenge. Markers of endothelial activation, platelet function, and nitric oxide degradation were measured in blood sampled from the pulmonary artery. Results: 19 of the patients (mean (SD) age, 56 (4) years; baseline mPAP, 34 (8) mm Hg; PVR, 420 (87) dyne.s.cm −5 ; CO, 6.4 (1.8) l/min) tolerated cold hand immersion for the maximum two minute duration. All 21 tolerated central cold pressor challenge (three to five injections of 10 ml saline boluses at 4°C). There was no significant change in haemodynamics after cold challenge by either route of provocation. Levels of endothelin-1, von Willebrand factor, fibrinogen, and 3-nitrotyrosine were raised compared with control values in patients with systemic sclerosis but without PAH, but did not change significantly after peripheral cold challenge. Conclusions: Pulmonary vasospasm in response to peripheral and centrally administered cold pressor challenge is unlikely to contribute to persistence of pulmonary arterial hypertension in patients with systemic sclerosis.